Fast spline quasicollocation solvers of integral equations - Vainikko, Gennadi; Zolk, Indrek (Mathematical Modelling and Analysis, 2007)
A fast (C, Cm) solver for linear Fredholm integral equations u = Tu+f with smooth data is constructed on the basis of a discrete version of the spline quasicollocation method. By a fast (C,Cm) solver we mean a discrete method that meets the optimal accuracy for f ∈ Cm with minimal arithmetic work. First Published Online: 14 Oct 2010